Comparative study of the circumferential and volumetric analysis between conventional casting and three-dimensional scanning methods for transtibial socket: A preliminary study - Mehmood, Waqas; Abd Razak, Nasrul Anwar; Lau, M.S.; Chung, Tze Yang; Gholizadeh, Hossein; Abu Osman, Noor Azuan (SAGE Publications, 2019)
Transtibial prosthetic sockets can be fabricated either by the conventional way, which involve using plaster of Paris bandages for casting. This will include modifications through hand, scanning and digital imaging of software. The aim of this study is to determine the circumferential profiles and conduct a volumetric analysis of a conventional socket that has fabrication using biosculptor technology. In doing this, a male transtibial amputee, age 28 years old with stable health condition was studied, where circumferential measurements were taken at intervals of 1 cm from the distal end of the residual limb to the medial tibial plateau level. Furthermore, the interior volume of both sockets and residuum were determined directly using water displacement method. A comparative value for the calculation of volume was also carried out using engineering mathematical equations. From these measurements, a total surface bearing transtibial sockets was fabricated to compare the changes of circumferential values of both sockets. The finding shows a percentage of the difference between the volume of the residual limb and conventional sockets to be 6.09%, whereas the biosculptor fabrication socket was 7.84% using the water displacement method. A comparison of circumferential profiles and volumetric analysis findings on the contrary showed that socket fabricated using the biosculptor technology is interchangeable with the conventional socket with more advantages, where biosculptor technology produces cheaper sockets and faster process with digital function in the procedure, unlike the conventional manual technique. © IMechE 2018.